Exotic populations in globular clusters: blue stragglers as tracers of the internal dynamical evolution of stellar systems. Issue Volume 10:Issue S312(2014) (7th March 2016) - Ferraro, Francesco R.
Abstract: In this paper I present an overview of the main observational properties of a special class of exotic objects (the so-called Blue Straggler Stars, BSSs) in Galactic Globular Clusters (GCs). The BSS specific frequency and their radial distribution are discussed in the framework of using this stellar population as probe of GC internal dynamics. In particular, the shape of the BSS radial distribution has been found to be a powerful tracer of the dynamical evolution of stellar systems, thus allowing the definition of an empirical "clock"able to measure the dynamical age of stellar aggregates from pure observational properties.